A review of age estimation methods in marine mammals with special reference to monodontids - Read, Fiona L.; Hohn, Aleta A.; Lockyer, Christina H. (NAMMCO Scientific Publications, 2018)
This paper presents a critical review of methods for estimating absolute or relative age in marine mammals. Absolute age is achieved by counting growth layer groups (GLGs) in hard structures such as teeth, ear plugs, baleen, bones and claws. Relative age can be obtained by methods such as aspartic acid racemisation, genetic telomeres, bone mineral density, fatty acid signatures and other methods. Each method is discussed in detail. Accuracy and precision, including inter-reader calibration and anomalies, as well as methods of validating GLG deposition rates are also addressed. Each section concludes with methods of age estimation applicable to monodontids, and suggestions on the focus of future age-estimation research.